Study of Antimicrobial Resistance (AMR) in Shigella spp. in India - Vaja, Maulikkumar D.; Chokshi, Heenaben A.; Jansari, Janak J.; Dixit, Om S.; Savaliya, Shubham S.; Patel, Deepak P.; Patel, Fenil S. (Recent Advances in Anti-Infective Drug Discovery, 2024)
Antimicrobial agents are essential in reducing illness and mortality brought on by infectious diseases in both humans and animals. However, the therapeutic effect of antibiotics has diminished due to an increase in antimicrobial drug resistance (AMR). This article provides a retrospective analysis of AMR in Shigella infections in India, showing a rise in resistance that has contributed to a global burden. Shigella spp. are widespread and the second-leading cause of diarrheal death in people of all ages. The frequency and mortality rates of Shigella infections are decreased by antibiotic treatment. However, the growth of broad-spectrum antibiotic resistance is making it more difficult to treat many illnesses. Reduced cell permeability, efflux pumps, and the presence of enzymes that break down antibiotics are the causes of resistance. AMR is a multifaceted and cross-sectoral problem that affects humans, animals, food, and the environment. As a result, there is a growing need for new therapeutic approaches, and ongoing surveillance of Shigella spp. infections which should definitely be improved for disease prevention and management. This review emphasizes on the epidemiological data of India, and antimicrobial resistance in Shigella spp.
Keywords: multidrug resistant (MDR) Shigella